Synthesis and Infrared Performance of SiB6 Powder through “Chemical Oven” Self-Propagating Combustion - Shuang Shuang; Fengxia Yang; Zhiwei Li; Jiangtao Li; Xiangmin Meng (Advances in Materials Science and Engineering)
SiB6 powders were prepared by the “chemical oven” method from Si and B powders. Here combustion with acid pickling “two-step” mode replaces the traditional synthesis method which helps to avoid severe condition of high temperature and high pressure. It could realize maximum reaction temperature to about 2000°C, and the whole process just needs ∼30 s. The average diameter of products is ∼10 μm. And the raw material Si and B are ∼3 μm and ∼20 μm, respectively. The infrared emissivity of products was evaluated by UV-vis spectrum with absorption band around 250∼2500 nm. All five samples show higher emissivity over UV-visible light range with lower emissivity over near-infrared range. Typically, the sample’s Si/B ratio of 1 : 1 shows highest integral intensity for about 0.85 compared with other molar ratios. It can be used as a more simple and effective method to obtain infrared ceramic SiB6 with high emissivity.